CORONARY ARTERY DISEASE IN PATIENTS OF PERIPHERAL ARTERIAL DISEASE: AN OBSERVATIONAL STUDY - AKHUND , N; ASHRAF, A; SHAMIM, A (Biological and Clinical Sciences Research Journal, 2023)
This study assessed the frequency of coronary artery disease in patients with peripheral arterial disease undergoing angiography. The study was carried out between January 2019 and June 2019, at the Department of Cardiology, MTI-KTH, Peshawar, on 149 patients who met the operational characteristics of PAD as stated were enrolled in the study through the outpatient and accident and emergency departments before being admitted to the cardiology ward for additional assessment. The patients were informed of the study's goals and advantages, and written informed consent was taken. Patients underwent coronary angiography in the same setting through the femoral or radial artery approach electively. The mean and SDs for age were 51 ±10.92, whereas the disease duration was 4±1.58. The mean and SDs for BMI were 29.4±1.07. 114 (76.51%) patients were found to be hypertensive, whereas 35 (23.48%) patients had normal blood pressure. 133 (89.26%) patients had diabetes, while 17 (10.73%) patients were non-diabetic. 91 (61.07%) patients were found to be smokers, whereas 58 (38.92%) patients were nonsmokers. 80 (53.69%) patients were recorded with coronary artery disease (CAD). It is concluded that scrutiny must be concentrated on the concomitant likelihood of coronary artery disease in patients with diagnosed severe peripheral arterial disease. Moreover, non-invasive coupled with invasive investigation must also be carried out to lessen the burden of this condition regarding morbidity and mortality.